The Proof is in the Plans: A New Method for Comparative Analysis of Historic Ship Plans - Jorgensen, Ida Christine (The international journal of nautical archaeology, 2025)
While 18th-century ship plans have mainly been regarded as written sources or used as illustrations, approaching these plans as archaeological artefacts reveals much more about the design and, critically, about the humans behind it. This paper presents a method, using readily available material and software, to digitally compare historic ship plans, answering questions about where shipbuilding knowledge came from, challenging traditions, and putting the warship design at the forefront of the research.